Efficient chosen-ciphertext secure proxy re-encryption scheme - Wei-wei ZHANG; Ru ZHANG; Jian-yi LIU; Xin-xin NIU; Yi-xian YANG (Tongxin xuebao)
In order to construct an efficient and chosen-chiphertext secure unidirectional re-encryption scheme in the standard model,a novel and efficient unidirectional proxy re-encryption scheme was proposed, and its chosen-ciphertext security in the adaptive corruption model was proved in the standard model. Compared with LV scheme, this scheme has the advantages of both higher efficiency and stronger curity. Under the same security level, this scheme has lower computational cost than that of WJ scheme.